Micro-hydrokinetic turbine potential for sustainable power generation in Malaysia - Salleh, M.B.; Kamaruddin, N.M.; Mohamed-Kassim, Zulfaa (IOP Publishing, 2018)
Micro-hydrokinetic turbine (μ-HKT) technology is considered a viable option for sustainable, green and low cost power production. In recent years, there is growing number of research and development on this technology to replace conventional power production systems such as fossil fuel as well as to provide off-grid electrification to communities in remote areas. This paper provides an overview of μ-HKT system, the implementation of the technology and the potential of using μ-HKT in Malaysia. A review on the climate in Malaysia shows that its average annual rainfall is higher than the world's average annual rainfall. It contributes to the total hydropower resource of about 29,000 MW which is available all year-round. Currently, hydropower resource contributes only 7.4% of the total electrical power production in Malaysia but is expected to increase with the main contribution coming from μ-HKT. However, the μ-HKT technology has not been adopted in Malaysia due to some challenges that hinder the development of the system. This paper reviews the μ-HKT technology and its potential for application in Malaysia, particularly in remote areas.